2022
DOI: 10.3390/v14030628
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Differences in Predictive Value of the C2HEST Score in Subjects with COVID-19—A Secondary Analysis of the COLOS Study

Abstract: Background: Since the outbreak of the COVID-19 pandemic, a growing number of evidence suggests that COVID-19 presents sex-dependent differences in clinical course and outcomes. Nevertheless, there is still an unmet need to stratify the risk for poor outcome at the beginning of hospitalization. Since individual C2HEST components are similar COVID-19 mortality risk factors, we evaluated sex-related predictive value of the score. Material and Methods: A total of 2183 medical records of consecutive patients hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, recently, Liang et al [ 7 ] demonstrated that C 2 HEST score could also predict adverse clinical outcomes, including death and hospitalization, among patients with heart failure. Considering that individual components of the C 2 HEST (C2: CAD/COPD; H: Hypertension; E: Elderly (Age ≥ 75); S: Systolic HF; T: Thyroid disease) are parallel to COVID-19 mortality risk factors, juxtaposing it with the outcomes of recently published studies [ 8 , 9 , 10 ] suggesting that this simple scoring system has the ability to predict outcomes in several COVID-19 subpopulations, we designed this study to evaluate the predictive value of C 2 HEST score in patients with heart failure (HF).…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, Liang et al [ 7 ] demonstrated that C 2 HEST score could also predict adverse clinical outcomes, including death and hospitalization, among patients with heart failure. Considering that individual components of the C 2 HEST (C2: CAD/COPD; H: Hypertension; E: Elderly (Age ≥ 75); S: Systolic HF; T: Thyroid disease) are parallel to COVID-19 mortality risk factors, juxtaposing it with the outcomes of recently published studies [ 8 , 9 , 10 ] suggesting that this simple scoring system has the ability to predict outcomes in several COVID-19 subpopulations, we designed this study to evaluate the predictive value of C 2 HEST score in patients with heart failure (HF).…”
Section: Introductionmentioning
confidence: 99%